TEKNOLOGI REKLAMASI LAHAN BEKAS TAMBANG NIKEL UNTUK MEMPERCEPAT KEBERHASILAN REKLAMASI - Suwardi; Randrikasari, Octaviana (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2023)
Nickel is formed through the weathering of ultrabasic or ultramafic rocks originating from oceanic crust which is transferred to the surface of continental crust. This formation process took millions of years, starting when ultramafic rocks were exposed on the earth's surface. Nickel mining plays an important role in the electric vehicle battery industry and economy in Indonesia, but its impact on the environment often results in mined land with unique characteristics that is difficult to reclaim. Ex-mining land often has a Mg/Ca ratio higher than one. In addition, the soil on ex-nickel mining land is usually shallow and hydrophobic, making it difficult to absorb water. Reclamation of ex-mining land is the focus to restore, increase the soil's water absorption capacity and land productivity. With an approach to improving physical, chemical, and biological properties, reclamation technology includes the method of making planting holes measuring 60x60x60 cm, composting organic materials, and using Super Absorbent Polymer (SAP) to increase the soil's water absorption capacity. In this context, reclamation technology is the key to accelerating the successful reclamation of ex-nickel mining land in a sustainable manner and optimizing the utilization of nickel mining resources in Indonesia.